SINTESIS DAN KARAKTERISASI SENYAWA KOMPLEKS Cu(II)-8- HIDROKSIKUINOLIN DAN Co(II)-8-HIDROKSIKUINOLIN - Agustina, Laelatri (Chem Info Journal, 2013)
Has done research about the synthesis and characterization of complex compounds of Cu(II)-hydroxyquinoline and Co(II)-8-hydroxyquinoline. This research was conducted to obtain complex compounds Cu(II)-8-hydroxyquinoline and Co(II)-8-hydroxyquinoline and knowing the character of the complex compounds through analysis of UV-Vis, AAS and FTIR. Synthesis of Cu(II)-8-hydroxyquinoline is done by mixing CuSO4.5H2O and 8-hydroxyquinoline ligand in methanol, and then performed with magnetic stirrer, filtered, washed and dried in a desicator. Synthesis of complexes Co(II)-8-hydroxyquinoline done the same way, with the starting materials CoSO4.7H2O. The results is obtained precipitated Cu(II)-8-hydroxyquinoline is green-yellow and Co(II)-8-hydroxyquinoline is yellow. UV-Vis analysis results of Cu(II)-8-hydroxyquinoline have a maximum wavelength at 394 nm, while maximum wavelength of Co(II)-8-hydroxyquinoline at 311 nm and 373 nm. FTIR analysis results indicate the presence of N atom and O atom of C-O clusters in 8-hydroxyquinoline ligand. The stability constants of Cu(II)-8-hydroxyquinoline of 1.206 x 105 while the Co (II)-8-hydroxyquinoline of 1.1299 x 104.